Toolpath allocation and scheduling for concurrent fused filament fabrication with multiple extruders. (1st February 2019) - Jin, Yu; Pierson, Harry A.; Liao, Haitao
ABSTRACT: Fused filament fabrication, like most layer-wise additive manufacturing processes, is hindered by low production rates and scalability issues. Concurrent fused filament fabrication mitigates these disadvantages by distributing the processing of each layer among multiple extruders working in parallel. The objective of this work is to develop a general toolpath allocation and scheduling methodology to achieve this objective. Breaks in a toolpath that are inherently created by slicing software for single-extruder machines are used to form sub-paths, and the assignment of these to available extruders is formulated as a scheduling problem with collision constraints. A formal optimization model is presented, and two novel heuristics are developed to obtain approximate solutions. Three case studies demonstrate the application of these algorithms and compare their relative performance with respect to fabrication time and computational cost. In simulations with three extruders, layer printing times were reduced by as much as 60% compared with single-extruder machines. The proposed heuristics also exceeded the performance of two baseline toolpath scheduling algorithms by as much as 45%. Two key layer characteristics were found to influence heuristic performance, and the advantages and disadvantages of each algorithm are discussed in the context of these characteristics.